Press Reader Product Demo,19 February 2016 - Universiti Malaysia Sarawak, Centre for Academic Information Services (Centre for Academic Information Services (CAIS), 2016)
Product demo on Press Reader have been held on 19th February 2016, 9.30am at Santubong computer lab, Level G CAIS. Press Reader contains of International content on any device: 4000+ titles from around the world, in 60+languages. The demo was conducted by Mr. Victor YF Liew, The Leading Bookstore Sdn Bhd.